Malignant phyllodes tumors with sarcomatous components: A histopathologic and molecular study - Ting Lei; Yunjie Song; Zhiyi Shen; Yongqiang Shi; Cunyan Xia; Xu Deng; Wenyue Da; Yan Peng; Qing Li (Translational Oncology)
Background: Malignant phyllodes tumors (MPTs) with sarcomatous components are often associated with substantial risks for local and distant recurrences. A more comprehensive characterization of their clinicopathological features and molecular profiles may offer significant potential innovative therapeutic strategies. Methods: A total of ten cases were collected with eight cases undergoing DNA next-generation sequencing (NGS). The clinicopathological characteristics, prognostic information, and genomic profiles were compared to those of MPTs without sarcomatous components. Results: Compared to MPT without sarcomatous components, no significant differences were found in age, tumor position, tumor size, menopausal status, or presence of fibroadenoma (p > 0.05). MPTs with osteosarcoma components had a poor prognosis either compared with other sarcomatous components (p = 0.027) or MPTs without sarcomatous components (p = 0.033). A notably high frequency of mutations was observed in several key genes within MPTs exhibiting sarcomatous components: TP53 (n = 6, 75.0 %), MUC16 (n = 4, 50.0 %), PTCH1 (n = 3, 37.5 %), and APC (n = 3, 37.5 %). In MPTs characterized by sarcomatous components, MCL1 (n = 6, 75.0 %) and MYC (n = 5, 62.5 %) demonstrated a notably high frequency of amplification. The NOTCH signaling pathway was significantly associated with MPTs characterized by sarcomatous components (13.6 % vs 75.0 %, p = 0.001). Conclusions: The presence of an osteosarcoma component may serve as an indicator for unfavorable prognosis. Activating mutations in TP53 have been identified in these tumors. Furthermore, it typically facilitates tumor formation and progression via the NOTCH signaling pathway. These findings may offer valuable insights for clinical prognosis and identify potential therapeutic targets.